“sistema de información web de control de personal y planillas para mejorar la gestión de recursos humanos del gobierno provincial de bagua grande” - Martell Ramírez, Abel Alejandro (2016)
The development of this research called "WEB SYSTEM INFORMATION OF PERSONAL AND WORKSHEETS CONTROL TO IMPROVING HUMAN RESOURCE MANAGEMENT OF PROVINCIAL GOVERNMENT OF BAGUA GRANDE" aims to improve the management of human resources, proposing a solution that influences significantly in the current model. Currently Sub Human Resources Management of the municipality presents some problems in processing payroll and personnel assistance. These problems are specified below. The current system of personal support information is independent personnel payroll system. In addition to there not an efficient control over the permissions of staff so the information system is inadequate for managing staff assistance. This leads to considerable time care in preparing a list. Since this problem has been appropriate and necessary to analyze, design and implement a Web information system to improve the management of the human resources of the Provincial Government of Bagua Grande and thus overcome the above problems. This thesis has continued his study under the guidelines of the RUP (Rational Unified Process) and for the design and modeling diagrams has made use of UML (Unified Modeling Language). Finally as a result of this study we conclude that by implementing the proposed system will achieve better management of Sub human resources of the Provincial Government of Bagua Grande generating savings in time and effort and allowing real control of information.